Commercialization of rice and nutrition: A case from West Kenya - Niemaijer, Rudo; Hoorweg, Jan (International Food Policy Research Institute, 1994)
The Kenyan government has actively encouraged cultivation of cash crops as part of its past and present development policies. Cash crop production of industrial and food crops has grown steadily, although the share of agricultural production that is marketed is still less than 50 percent (Kenya, Central Bureau of Statistics 1988). This chapter studies the cultivation of commercial rice at large irrigation schemes in Nyanza Province, western Kenya.